Association between bruxism and symptomatic gastroesophageal reflux disease: A case-control study. (October 2018) - Li, Yuanyuan; Yu, Fan; Niu, Lina; Long, Yong; Tay, Franklin R.; Chen, Jihua
Abstract: Objectives: To examine the relation between bruxism and gastroesophageal reflux disease (GERD) and the contribution of depression, anxiety and impaired sleep quality to that association. Methods: A three-centre case-control study was conducted consisting of 887 consecutive clinically-diagnosed bruxism patients aged 18–75 years and 887 matched controls. Diagnosis of GERD was based on the Montreal definition: moderate/severe symptoms ≥ one day/week or mild symptoms ≥ two days/week. Logistic regression was used to evaluate the association between bruxism and GERD. Mediation analyses were used to test whether the association between bruxism and GERD was mediated by depression, anxiety or impaired sleep quality. Results: Binary logistic regression identified that GERD was associated with bruxism (odds ratio, 6.87; 95% confidence interval (CI), 4.34–10.88). This association was stronger in females (odds ratio, 12.27; 95% CI, 5.81–25.91) than in males (odds ratio, 3.99; 95% CI, 2.17–7.32). Multinomial logistic regression identified that GERD was associated with all types of bruxism (sleep bruxism alone, odds ratio, 6.71, 95% CI, 4.22–10.68; awake bruxism alone, odds ratio, 13.06, 95% CI, 5.32–32.05; overlap of sleep bruxism and awake bruxism, odds ratio, 6.48, 95% CI, 3.05–13.77). Ordinal logistic regression identified that longer GERD duration (> 2 years vs ≤ 2 years) was associated with bruxism frequency (odds ratio, 1.50; 95% CI, 1.10–2.05). Mediation analyses found that the association between bruxism and GERD was partially-mediated through depression, anxiety and impaired sleep quality. Conclusions: Clinically-diagnosed bruxism is associated with symptomatic GERD and is partially-mediated through depression, anxiety and impaired sleep quality. Clinical Significance: Because bruxism is strongly associated with symptomatic GERD and patients with frequent bruxism symptoms tend to suffer from GERD for extensive time-periods, dentists should consider evaluation of GERD status as an elemental part of the medical examination of bruxism, especially severe bruxism.